2008
DOI: 10.2174/1875397300802010051
|View full text |Cite
|
Sign up to set email alerts
|

A High Throughput Serum Paraoxonase Assay for Discovery of Small Molecule Modulators of PON1 Activity

Abstract: PON1 has been demonstrated to be the serum enzyme responsible for detoxifying organophosphate chemical weapons and plays a protective role against atherosclerosis. In order to identify small molecules that modulate PON1 activity in serum, we developed a high throughput kinetic absorbance assay using mouse serum and the organophosphate paraoxon. The IC50 value obtained for the known PON1 inhibitor, 2-hydroxyquinoline, matched the value reported for purified PON1. A compound library was screened resulting in no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…First, we confirmed that treatment with 2-hydroxyquinoline inhibited 90% of PON1 activity in HDL. This inhibition rate was compatible with a previous report 26) . The lag duration time of HDL from probucol-treated patients was reduced by 40% with 2-hydroxyquinoline treatment (Fig.…”
Section: Sources Of Fundingsupporting
confidence: 93%
See 2 more Smart Citations
“…First, we confirmed that treatment with 2-hydroxyquinoline inhibited 90% of PON1 activity in HDL. This inhibition rate was compatible with a previous report 26) . The lag duration time of HDL from probucol-treated patients was reduced by 40% with 2-hydroxyquinoline treatment (Fig.…”
Section: Sources Of Fundingsupporting
confidence: 93%
“…A specific inhibitor of PON1 25,26) , 2-hydroxyquinoline (Sigma-Aldrich Corp., St. Louis, MO) was diluted in methanol (10 mM). This stock solution was diluted in PBS.…”
Section: Inhibition Of Pon1 Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the data presented here does not support the notion that direct interactions between anthocyanins and/or their metabolites affect the lactonase or arylesterase activity of PON1, it is not conclusive. The purified enzyme used here is not in its native environment which would include the presence of HDL and the ApoA1 protein, and this may affect the enzyme structural conformation and its stability and therefore its activity [60][61][62][63][64]. In theory it would be possible to use instead serum as a source of PON1.…”
Section: Discussionmentioning
confidence: 99%
“…Paraoxonase 1 (PON1) was selected in this study for further characterization owing to its primary location of synthesis in the liver and its association with high‐density lipoprotein (HDL) metabolism after secretion into plasma. HDL‐associated PON1 has been reported to reduce oxidative stress in lipoproteins and atherosclerotic lesions . The PON1 gene is activated by PPAR‐γ, which increases the synthesis and release of PON1 enzyme from the liver, thereby reducing atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%